Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41467-018-05395-y
|View full text |Cite
|
Sign up to set email alerts
|

The chimeric TAC receptor co-opts the T cell receptor yielding robust anti-tumor activity without toxicity

Abstract: Engineering T cells with chimeric antigen receptors (CARs) is an effective method for directing T cells to attack tumors, but may cause adverse side effects such as the potentially lethal cytokine release syndrome. Here the authors show that the T cell antigen coupler (TAC), a chimeric receptor that co-opts the endogenous TCR, induces more efficient anti-tumor responses and reduced toxicity when compared with past-generation CARs. TAC-engineered T cells induce robust and antigen-specific cytokine production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 50 publications
2
68
0
1
Order By: Relevance
“…Their studies demonstrated that the use of OKT3 in this setting produced poor proliferation and cytokine production, and that UCHT1 TACs demonstrated superior performance in preclinical models of solid and hematological tumors. 31 In our study, we demonstrate that B7-H7 cotreatment with OKT3 has opposing outcomes when compared with cotreatment with UCHT1, which could be explained by discrepancies in epitope specificity and the strength of the signal delivered by the different α-CD3 clones. In addition, as discussed later, we believe that OKT3 is the superior clone that should be used in these assays, as it reflects the biological outcomes of in vitro physiological assays.…”
Section: Discussionmentioning
confidence: 66%
“…Their studies demonstrated that the use of OKT3 in this setting produced poor proliferation and cytokine production, and that UCHT1 TACs demonstrated superior performance in preclinical models of solid and hematological tumors. 31 In our study, we demonstrate that B7-H7 cotreatment with OKT3 has opposing outcomes when compared with cotreatment with UCHT1, which could be explained by discrepancies in epitope specificity and the strength of the signal delivered by the different α-CD3 clones. In addition, as discussed later, we believe that OKT3 is the superior clone that should be used in these assays, as it reflects the biological outcomes of in vitro physiological assays.…”
Section: Discussionmentioning
confidence: 66%
“…Researchers speculated that CAR-T cell toxicity is related to the synthetic nature of the receptor design. Therefore, a new type of CAR-T cells has been designed with an MHC-independent receptor T cell antigen coupler, which can co-opt the endogenous TCR and exert antitumor effect with fewer toxic reactions [ 116 ]. Other AEs include persistent cytopenia, hypogammaglobulinemia, and inflammation; all these could be managed through appropriate supportive treatments but need close monitoring.…”
Section: Chimeric Antigen Receptor (Car)-t Cellsmentioning
confidence: 99%
“…Also, receptor potentiation by proteolysis of a small masking tag degraded in the presence of specific proteases expressed in the tumor microenvironment was elegantly demonstrated for an EGFR-specific CAR [300]. Recently, Helsen et al reported the use of a T-cell antigen coupler (TAC) chimeric receptor [301] which consists of a double targeting moiety: an antigen-specific scFv followed by a CD3-activating scFv built on a CD4 scaffold. Such TAC could recognize a defined tumor antigen on the target cell using the endogenous TCR signaling pathway rather than an artificial signal mediated by classical CD28/CD3z signaling moiety.…”
Section: Control Of Transgene Expression and T-cell Functionmentioning
confidence: 99%